How youth-led climate movements played a role in the passage of the United States’ first ever climate bill, the Inflation Reduction Act - Mélanie Meunier (Revue LISA)
On August 16, 2022, President Joe Biden signed the Inflation Reduction Act. In terms of climate action, this is truly a game-changing achievement, which in all probability, would not have passed in Congress without the massive mobilization of American youths. Given the recurring failure of the federal government to pass a climate law, low expectations of the 117th Congress’ success in 2022 were widespread. The United States, compared to most OECD nations, is an outlier in its relative lack of support for climate measures. Polls show that global warming and climate change have never yet been the top priority for Americans as a whole. The extreme anti-environmental agenda of the Trump administration, of Republicans in power, and most recently of the Supreme Court, alarmed many Americans, and propelled scores of young people into the climate movement. Not only was there a crisis of global warming, but also one of representation and of democracy itself. Many youths were galvanized to act against the forces that were threatening their future and that of their country. This paper will attempt to show that, without the massive mobilization of American youths at multiple levels, from school strikes to concerted get-out-the vote campaigns to sustained pressure on elected officials, this climate law would not have passed. This article will explore the elements that motivated youth leaders to put their lives on hold and devote themselves entirely to the climate crisis before concentrating on the strategies that succeeded in achieving significant results – namely, passage of the Inflation Reduction Act – that had eluded the youth activists’ predecessors.